2017
DOI: 10.1001/jamapediatrics.2016.3643
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bystander Cardiopulmonary Resuscitation With Overall and Neurologically Favorable Survival After Pediatric Out-of-Hospital Cardiac Arrest in the United States

Abstract: IMPORTANCE There are few data on the prevalence or outcome of bystander cardiopulmonary resuscitation (BCPR) in children 18 years and younger. OBJECTIVE To characterize BCPR in pediatric out-of-hospital cardiac arrests (OHCAs). DESIGN, SETTING, AND PARTICIPANTS This analysis of the Cardiac Arrest Registry to Enhance Survival database investigated nontraumatic OHCAs in children 18 years and younger from January 2013 through December 2015.EXPOSURES Bystander CPR, which included conventional CPR and compression-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
5
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 31 publications
1
85
5
7
Order By: Relevance
“…The authors compared bystander-administered chest compression-only CPR and CPR using chest compressions with rescue breaths. 7 The cohort was analyzed on the basis of age: <1 or 1 to 18 years. For infants, CPR using chest compressions with rescue breaths was better than no CPR but was no different from chest compression-only CPR for favorable neurological outcome.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…The authors compared bystander-administered chest compression-only CPR and CPR using chest compressions with rescue breaths. 7 The cohort was analyzed on the basis of age: <1 or 1 to 18 years. For infants, CPR using chest compressions with rescue breaths was better than no CPR but was no different from chest compression-only CPR for favorable neurological outcome.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…The patient populations and/or pathologies evaluated in the 66 studies included in the final review were: general PICU patients (n=15 studies) (923), seizures and/or status epilepticus (SE) (n=7) (2430), traumatic brain injury (TBI) (n=17) (3147), cardiac arrest (n=22) (4869), and infectious diseases (n=5) (7074). …”
Section: Resultsmentioning
confidence: 99%
“…There are significant ongoing efforts to optimize emergency medical systems of care and therapies aimed at improving outcomes after pediatric out-of-hospital cardiac arrest. Successes are starting to be reported in increased utilization of bystander cardiopulmonary resuscitation leading to improved overall survival and survival with favorable neurologic outcomes (69). …”
Section: Neurologic Outcomes Following Picu Carementioning
confidence: 99%
“…Meyer et al 3 found a higher rate (26.9%) in a study from Washington,3 while another study from US Cardiac Arrest Registry to Enhance Survival database reported an overall survival rate of 11.3% 33. A recent population-based studies from Sweden described a survival rate of 14.0% in patients 21 years old and younger 23.…”
Section: Discussionmentioning
confidence: 96%